2020
DOI: 10.15358/2511-8676-2020-4-205
|View full text |Cite
|
Sign up to set email alerts
|

Branded Employee Behaviour as a Double-Edged Sword: How Perceptions of Service Employees Impact Job Seekers' Application Intentions

Abstract: Prior brand experiences affect job seekers’ application decisions, as they recall service encounters with brands which they have experienced as customers. As brand representatives, service employees play a critical role in these recollections. Their behaviour might inform job seekers’ understanding of the employer brand, thereby affecting their application decision. The impact of the service employee’s behaviour might be even more impactful if this behaviour is branded, meaning that the employee’s appearance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Moreover, research showed that consistent employee behavior positively influences brand trustworthiness of job seekers (Wünderlich et al , 2020), and customer trust can positively influence WOM about a company (Gremler et al , 2001). Furthermore, trust is proposed as an important mediating variable between customer perception of CSR and their attitude toward a company (Kim et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, research showed that consistent employee behavior positively influences brand trustworthiness of job seekers (Wünderlich et al , 2020), and customer trust can positively influence WOM about a company (Gremler et al , 2001). Furthermore, trust is proposed as an important mediating variable between customer perception of CSR and their attitude toward a company (Kim et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given the latter’s growing awareness and preference for sustainability, this finding underlines the importance of SMO-aligned employee behavior in sustainable service organizations. Thus, when companies recruit service employees, it is advisable that they select applicants who can identify themselves with the corporate values, since they could behave in a more authentic way (Wünderlich et al , 2020). In other words, they probably trust these values, which can spill over to customers and leads to positive WOM, in turn, as our study showed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations